New user? Sign up

Existing user? Sign in

If \(a+b=c\) then \[{ a }^{ 3 }+{ b }^{ 3 }\overset { ? }{ = }{ c }^{ 3 }={ \left( a+b \right) }^{ 3 }\]

Note by JohnDonnie Celestre 2 years ago

Sort by:

try again what do you ask

Log in to reply

I can't understand the last statement starting from "so this problem is equivalent to .. "

I do not understand what you are trying to ask.

I can't understand why is \(a^3 + b^3 = c^3\) equates to \((a+b)^3 = c^3\) if \(a+b=c\). I really tried hard to understand but I failed.

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewesttry again what do you ask

Log in to reply

I can't understand the last statement starting from "so this problem is equivalent to .. "

Log in to reply

I do not understand what you are trying to ask.

Log in to reply

I can't understand why is \(a^3 + b^3 = c^3\) equates to \((a+b)^3 = c^3\) if \(a+b=c\). I really tried hard to understand but I failed.

Log in to reply